Case report: bullous pemphigoid development underlies dystrophic epidermolysis bullosa disease worsening - Di Zenzo, Giovanni; Floriddia, Giovanna; Rossi, Sabrina; Mariotti, Feliciana; Primerano, Alessia; Condorelli, Angelo Giuseppe; Didona, Biagio; Castiglia, Daniele (Frontiers in Immunology, 2022)
Autoimmune response to cutaneous basement membrane components superimposed on a genetic skin fragility disease, hereditary epidermolysis bullosa (EB), has been described, but its effects on disease course remain unclear. We report a 69-year-old individual with congenital skin fragility and acral trauma-induced blistering, which had suddenly worsened with onset of severe itch and diffuse spontaneous inflammatory blisters. Next generation sequencing identified compound heterozygous null and missense COL7A1 mutations, allowing diagnosis of recessive dystrophic EB. However, patient’s clinical history prompted us to investigate whether he might have developed a pathological autoimmune response against basement membrane components. Tissue-bound and circulating IgG antibodies to the major bullous pemphigoid (BP) antigen, BP180, were detected in patient’s skin and serum, respectively, consistent with a diagnosis of BP. Corticosteroid therapy was initiated resulting in remission of BP manifestations. EB patients presenting rapid disease worsening should be investigated for development of a concomitant autoimmune blistering disease.